Analisis Pengaruh Pendidikan dan Pelatihan Terhadap Kinerja Pegawai di Sudin Perhubungan Jakarta Selatan - A. Fauzan Fadlan fauzan; Moch Najiallah; Bobby Reza (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Education and training are the most important factors in improving the performance of South Jakarta Transportation Authority employees. The author's observations show that the percentage of employees with a secondary school diploma/equivalent is still high, and there are still many employees who have not participated in any further training. The authors conducted this study to determine the impact of education and training on the performance of the South Jakarta transportation subdivision. In this study, the method used was a quantitative method. The tests used in this study used data validity tests, data reliability tests, classical hypothesis tests, and hypothesis tests. The results of the study partially show that educational factors have no effect on employee performance, while educational factors do have an effect on employee performance. Parallel studies have shown that both education and training have an impact on employee performance. The authors hope that the findings of this study will help public authorities make policy decisions related to education and training and inform future researchers.